Combination Chemotherapy in Severe Pulmonary Vein Stenosis-A Case Series - Gabriel Krivenko; Karen Iacono; David Nykanen; Robyn Keen; Robert Sutphin; Michael Farias (MDPI AG, 2023)
Pulmonary vein stenosis results from a proliferative process that leads to the progressive obstruction of venous return to the left atrium. It is often resistant to catheterization and surgical based interventions and is frequently fatal when encountered in its severe form. Here, we describe three patients with severe, primary pulmonary vein stenosis that was progressing despite aggressive conventional management strategies. All three patients were initiated on combination chemotherapy with imatinib and sirolimus, drugs which have been previously shown to independently have potential benefit against PVS. Soon after the initiation of these therapies, all three patients experienced a stabilization of their disease process and clinical improvement. All three patients remain alive, with tolerable side effects from the medications. Although early in our experience and with only a small number of patients, combination chemotherapy with imatinib and sirolimus shows promise and merits further investigation as a therapeutic option for this aggressive disease.